EFEK AROMATERAPI KOMBINASI LAVENDER DENGAN SEREH TERHADAP KESEHATAN;LITERATUR REVIEW - Nadia Purnama Dewi; Dessy Abdullah; Ade Teti Vani; Rinita Amelia (Nusantara Hasana Journal, 2024)
Aromatherapy is one of the increasingly popular alternative methods in health management. Combining essential oils from lavender (Lavandula angustifolia) and lemongrass (Cymbopogon citratus) plants shows promising therapeutic potential. This article aims to assess the health effects of the combined aromatherapy of the two plants. The research includes the analysis of chemical components, physiological effects, and clinical applications of lavender and lemongrass essential oils.